1988
DOI: 10.1021/bi00413a004
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic branched-chain analogs of distearoylphosphatidylcholine: structure-activity relationship in inhibiting and activating protein kinase C

Abstract: A series of distearoylphosphatidylcholine (DSPC) analogues having various branched alkyl chains were synthesized and tested for their abilities to regulate protein kinase C (PKC). The greatest improvement (about 3-fold) in the PKC inhibitory activity over that seen for the parental lipid (i.e., DSPC) was accomplished by substitution of 8-methylstearate at sn-2 and 16-methylstearate at both sn-1 and sn-2 positions of glycerol; substitutions at both sn-1 and sn-2 with 8-methylstearate, on the other hand, caused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

1988
1988
2006
2006

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…Such bilayer dehydration could, in principle, favorably change the association of PK-C molecules with the lipids, leading to enzyme activation. It has also been previously shown that PK-C activity is increased by synthetic PC analogues with hydrophobic groups near the headgroups (Charp et al, 1988), which may be due to the promotion of nonbilayer lipid phases by such substitutions (Lewis et al, 1994) and/or a decrease in the association with water molecules. Relatively small numbers of water molecules associated with phosphatidylethanolamine headgroups was suggested to be the cause for the tendency of this lipid to form inverted hexagonal phases (Yeagle and Sen, 1986).…”
Section: Discussionmentioning
confidence: 93%
“…Such bilayer dehydration could, in principle, favorably change the association of PK-C molecules with the lipids, leading to enzyme activation. It has also been previously shown that PK-C activity is increased by synthetic PC analogues with hydrophobic groups near the headgroups (Charp et al, 1988), which may be due to the promotion of nonbilayer lipid phases by such substitutions (Lewis et al, 1994) and/or a decrease in the association with water molecules. Relatively small numbers of water molecules associated with phosphatidylethanolamine headgroups was suggested to be the cause for the tendency of this lipid to form inverted hexagonal phases (Yeagle and Sen, 1986).…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies (Charp, 1988;Munder and Westphal, 1990;Mollinedo et al, 1993;Engelmann et al, 1996) showed the biphasic effect of these compounds. We can conclude that the doses and the times of incubation could be the key of the use of ALPs.…”
Section: Discussionmentioning
confidence: 84%
“…These results are very interesting given our demonstration that the substitution of hydrophobic groups near the polar/apolar interfacial region of the lipid bilayer promotes the formation of nonlamellar phases and previous demonstrations that protein kinase C is activated by nonlamella-forming lipids (see ). Because the possibility that the lipids used by Charp et al, (1988) may have an enhanced nonlamella-forming potential was not recognized by the authors, it would be very interesting if their results were reevaluated with due consideration to the findings presented here.…”
Section: Discussionmentioning
confidence: 94%
“…Finally, the activity of protein kinase C was recently shown to be increased by diacyl PCs with hydrophobic groups near to the bilayer polar/apolar interface (Charp et al, 1988). These results are very interesting given our demonstration that the substitution of hydrophobic groups near the polar/apolar interfacial region of the lipid bilayer promotes the formation of nonlamellar phases and previous demonstrations that protein kinase C is activated by nonlamella-forming lipids (see ).…”
Section: Discussionmentioning
confidence: 99%